The Effectiveness of Psophocarpus Tetragonolobus’s Seed as Turbidity Removal - S, Kamel; Z. Z. M, Zaki; J, Kassim (International Journal of Engineering and Technology, 2018)
High turbidity in water not only will reduce the quality of water itself but it can give impact to the ecosystem as well. In water treatment, coagulation and flocculation are the process involved in removing turbidity. Chemical coagulant such as aluminium sulfate (Alum) and ferric chloride are effective way and widely used in order to remove the turbidity in water. However, these chemical coagulants have a side effect in spite of the effectiveness in turbidity removal, the usage of alum and other chemical coagulants bring concerns due to its impact to the environment, human health and economy. Therefore, natural coagulant is another alternative for turbidity removal in water treatment. Natural coagulant is a plant-based coagulant which can be used to replace chemical coagulants. These coagulants are generally cheaper and safer than chemical counterparts. This research is conducted to compare the effectiveness of natural based coagulant made from Psophocarpus tetragonolobus and chemical coagulant in improving the quality of raw water. Findings from this study showed P. tetragonolobus can remove turbidity up to 60 percent with 40 ml, 1% solution. Therefore, P. tetragonolobus can be considered as a potential resource for natural coagulant.Â Â